Differences of young adult smokers and non-smokers saliva reviewed by salivary pH, viscosity, and volume - Kusumaningrum, Dias Mareta; Tjahajawati, Sri; Rizali, Ervin (Padjadjaran Journal of Dentistry, 2019)
Introduction: Salivary pH, viscosity and volume play an important role in maintaining tooth and oral tissue integrity. The purpose of this research was to evaluate the difference of young adult smokers and non-smokers saliva reviewed by its pH, viscosity and volume. Methods: The research sample of 28 smokers and 24 non-smokers. Saliva was collected by spitting method then the pH, viscosity and volume was measured. The data was analyze using independent sample t-test and chi-square. Results: The result indicated that there was a significant difference in the mean value of salivary pH on smokers and non-smokers with p-value 0.000 (p < 0.05). There was a significant difference in the mean value of salivary viscosity on smokers and non-smokers with p-value 0.000 (p < 0.05.) There was a significant difference in the mean value of salivary volume on smokers and non-smokers with p-value 0.000 (p < 0.05). Conclusion: The conclusion of the research showed that salivary pH of smokers was lower than non-smokers, salivary viscosity of smokers was higher than non-smokers and salivary volume of smokers was fewer than non-smokers.Keywords: Young adult, smokers, non-smokers, saliva, salivary pH, salivary viscosity, salivary volume